2017
DOI: 10.1016/j.rbre.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Relevant aspects of imaging in the diagnosis and management of gout

Abstract: Gout is an inflammatory arthritis characterized by the deposition of monosodium urate crystals in the synovial membrane, articular cartilage and periarticular tissues leading to inflammation. Men are more commonly affected, mainly after the 5th decade of life. Its incidence has been growing with the population aging. In the majority of the cases, the diagnosis is made by clinical criteria and synovial fluid analysis, in search for monosodium urate crystals. Nonetheless, gout may sometimes have atypical present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This finding suggests that tophus is not the major cause of gouty dactylitis and also supports the fact that dactylitis is not a chronic hallmark of the disease such as tophus. [4] Although, we have observed that higher levels of blood uric acid are present in patients with PD signal, it is even more relevant to underline the fact that tenosynovitis and joint effusion was present in patients with levels of uric acid below the theoretical target. This observation could be confusing and can be interpreted from two different points of view: First, we can assume that, as some studies have suggested, the therapeutic goal in gout is still not enough to prevent musculoskeletal damage.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This finding suggests that tophus is not the major cause of gouty dactylitis and also supports the fact that dactylitis is not a chronic hallmark of the disease such as tophus. [4] Although, we have observed that higher levels of blood uric acid are present in patients with PD signal, it is even more relevant to underline the fact that tenosynovitis and joint effusion was present in patients with levels of uric acid below the theoretical target. This observation could be confusing and can be interpreted from two different points of view: First, we can assume that, as some studies have suggested, the therapeutic goal in gout is still not enough to prevent musculoskeletal damage.…”
Section: Discussionmentioning
confidence: 70%
“…The interpretation of findings was dichotomous in the determination of synovitis, tenosynovitis, and enthesopathy according to EULAR definition criteria. [10] The identification of tophi was made according to the definition of Fernandes et al [4] The overlapping of findings was counted independently at the moment of establishing the prevalence.…”
Section: Image Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…US can effectively identify crystal deposits related to gout and calcium pyrophosphate dihydrate. [54][55][56] In the pediatric population, US has been shown to have good agreement with MRI for evaluation of cartilage thickness in patients with juvenile idiopathic arthritis. [57][58][59] Meniscal Pathology…”
Section: Cartilaginous Pathologymentioning
confidence: 99%
“…This causes elevated levels of uric acid in the blood leading to hyperuricemia, which is defined as serum uric acid levels surpassing urate blood solubility (>6.8 mg/dl) (Burke et al, 2015;De Avila Fernandes et al, 2017;Lawrence et al, 2008;Wertheimer, Morlock, & Becker, 2013).…”
Section: Types Of Arthritismentioning
confidence: 99%